2015
DOI: 10.1096/fj.15-275180
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine‐1‐phosphate inhibits IL‐1‐induced expression of C‐C motif ligand 5viac‐Fos‐dependent suppression of IFN‐β amplification loop

Abstract: The neuroinflammation associated with multiple sclerosis involves activation of astrocytes that secrete and respond to inflammatory mediators such as IL-1. IL-1 stimulates expression of many chemokines, including C-C motif ligand (CCL) 5, that recruit immune cells, but it also stimulates sphingosine kinase-1, an enzyme that generates sphingosine-1-phosphate (S1P), a bioactive lipid mediator essential for inflammation. We found that whereas S1P promotes IL-1-induced expression of IL-6, it inhibits IL-1-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 64 publications
(91 reference statements)
2
13
0
Order By: Relevance
“…The expression and the release of CCL5 from astrocytes is tightly controlled by several receptor subtypes, including opioid receptors ( 49 , 50 ), group III metabotropic glutamate receptors ( 2 ), alpha/beta noradrenergic receptors ( 51 53 ), and sphingosine-1-phosphate receptor (S1PR) subtype 1 ( 54 ), as well as by endogenous neurotoxin such as quinolinic acid acting at NMDA receptors ( 55 ). These receptors represent targets of therapeutics for inflammatory autoimmune disease typified by overexpression of CCL5.…”
Section: Ccl5 Production In Cnsmentioning
confidence: 99%
“…The expression and the release of CCL5 from astrocytes is tightly controlled by several receptor subtypes, including opioid receptors ( 49 , 50 ), group III metabotropic glutamate receptors ( 2 ), alpha/beta noradrenergic receptors ( 51 53 ), and sphingosine-1-phosphate receptor (S1PR) subtype 1 ( 54 ), as well as by endogenous neurotoxin such as quinolinic acid acting at NMDA receptors ( 55 ). These receptors represent targets of therapeutics for inflammatory autoimmune disease typified by overexpression of CCL5.…”
Section: Ccl5 Production In Cnsmentioning
confidence: 99%
“…To identify CNS cell types altered during neuroinflammatory processes, we developed an unbiased in vivo screen based on transcription of c-Fos (Bullitt, 1990), an immediate-early gene (IEG) that is rapidly transcribed in response to cellular stimuli, independent of de novo protein synthesis (Lau and Nathans, 1987). c-Fos can be activated in astrocytes (McNaughton and Hunt, 1992; Anderson et al, 1994; Morishita et al, 2011; Yester et al, 2015), microglia (Eun et al, 2004), and oligodendrocytes (Muir and Compston, 1996), as well as within neurons associated with memory (Matsuo et al, 2008). We adapted a conditional c-Fos reporter mouse that historically marks cells with nuclear GFP, which could be followed in four-dimensional (3D over time) analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism by which SPHK1 suppresses STAT1 phosphorylation and downregulates total STAT1 levels remains to be further investigated, several pieces of evidence suggest that S1P might play an essential role. Indeed, recent studies have shown that activation of S1P 1 and S1P 2 by S1P suppresses IFN and STAT1 activity [77,78]. In addition, S1P binding to S1P 1 has also been shown to promote STAT3 activation [30,79,80], which is pro-tumorigenic in breast cancer [81].…”
Section: Discussionmentioning
confidence: 99%